2014
DOI: 10.1111/coa.12250
|View full text |Cite
|
Sign up to set email alerts
|

Hospital stay following complex major head and neck resection: what factors play a role?

Abstract: Clean-contaminated wound was the most significant factor affecting the LOS, with others being ASA grades 3 and 4, longer duration of surgery and presence of a tracheostomy. Using these parameters, it is possible to predict the LOS in patients undergoing major surgical resection for head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…This is comparable to another Australian study (median LOS of 29 days) but much longer than the LOS reported from studies in the USA, Canada and UK . The LOS following laryngectomy is affected by both patient and health service factors . These factors include: available healthcare resources, established care pathways, the availability of appropriate patient support services close to the patient's home and inpatient versus outpatient care models .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This is comparable to another Australian study (median LOS of 29 days) but much longer than the LOS reported from studies in the USA, Canada and UK . The LOS following laryngectomy is affected by both patient and health service factors . These factors include: available healthcare resources, established care pathways, the availability of appropriate patient support services close to the patient's home and inpatient versus outpatient care models .…”
Section: Discussionsupporting
confidence: 66%
“…The LOS following laryngectomy is affected by both patient and health service factors . These factors include: available healthcare resources, established care pathways, the availability of appropriate patient support services close to the patient's home and inpatient versus outpatient care models . In our study, there was significant disagreement between LOS predicted by the ACS‐NSQIP calculator and actual LOS.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Numerous analyses of large-scale databases of head and neck surgery patients have found expected factors associated with prolonged total LOS, such as older age, poorer functional status, alcohol consumption, increased comorbidities, longer operative time, blood transfusion, operative complications, wound types, preoperative radiation therapy (RT) (.60 Gy). [16][17][18][19][20] While these factors may influence the LOS up to the date eligible for DC, they are unlikely to lead to delays in DC once the patient is medically fit to leave the hospital. The current results reflect this as no comorbidities predicted DC delay (P .…”
Section: Discussionmentioning
confidence: 99%
“…This association potentially demonstrates patients with more complex surgical cases and medical conditions as well as social situations. [16][17][18][19][20] The magnitude of DC delay in these patients was nearly a week and suggests that by optimizing the medically necessary LOS, DC delays could be decreased.…”
Section: Discussionmentioning
confidence: 99%